A deep dive into CGIAR’s Climate Change Research Portfolio based on PRMS Data (2022-2023) - Koren, Judith; Jeanneau, Louise; Mukherji, Aditi (CGIAR System Organization, 2024)
Central to the CGIAR Climate Impact Platform's mandate is providing strategic guidance on portfolio management. In alignment with this objective, the PRMS database was utilised to build the 2022-2023 Climate Impact Platform's portfolio narrative story. Offering an analysis of the CGIAR 's climate outputs released in 2022 and 2023, the portfolio includes an overview of methods, solutions of focus, and impact areas, highlighting key stories and themes characterizing the 2022-2023 CGIAR climate research outputs.